膵臓癌を検出するためのマーカー (2016)
糖蛋白質Ｃ４ＢＰＡまたはＰＩＧＲを膵臓癌を検出するためのマーカーとして用いると、膵臓癌を慢性膵炎患者や健常者とを区別して特異的に判定することができる。また、手術後の膵臓癌患者の予後の状況をモニターすることができる。更には、他の膵臓癌マーカー、例えば、ＣＡ１９−９などと組み合わせて用いることにより、慢性膵炎患者や健常者とを区別してより特異的に判定することができる。 A marker for detecting pancreatic cancer, said marker comprising a glycoprotein C4BPA or PIGR, whereby a pancreatic cancer patient can be distinguished from a chronic pancreatitis patient or a normal subject and thus specifically diagnosed. Also, the marker is usable in monitoring the postoperative prognosis of a pancreatic cancer patient. When the aforesaid marker is used in combination with another pancreatic cancer marker such as CA19-9, furthermore, a pancreatic cancer patient can be distinguished from a chronic pancreatitis patient or a normal subject and diagnosed more specifically.